STRATEGI KOMUNIKASI ORGANISASI INKLUSIF CAFE ONNI HOUSE SURABAYA DALAM MELIBATKAN PENYANDANG DOWN SYNDROME UNTUK MAGANG SEBAGAI WAITRESS - Conny Brilliant Dwikananda, Kartika; Sunarto, Sunarto; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Organizations require effective communication strategies to achieve their missions and goals. By involving individuals with Down syndrome in a waitress internship program, organizations need to redefine their communication strategies and policies throughout the program to create an inclusive work environment for people with disabilities. Through statements from ten informants involved in the implementation of the collaborative program involving individuals with Down syndrome for a waitress internship, this qualitative research uses an intrinsic case study method within a post-positivist paradigm to find pattern matching from. Karl Weick and James Taylor's Theory of Organizational Sensemaking, Widhawati's Concept of Inclusive Environment, and Fred R. David's Strategic Communication Planning are chosen to help explore the theoretical review. Through research, show the stages of communication strategies carried out by ONNI House Surabaya in implementing an inclusive work environment. Through communication strategies starting from planning, implementation, and evaluation, ONNI House Surabaya successfully completed the program to involve Down syndrome trainees as waitresses.